Carbon (IV) oxide adsorption efficiency of functionalized HKUST-1, IRMF-1, and UiO-66 metal organic frameworks - Moyosore, Abdullahi; Ahmad, Haslina; Muhammad Latif, Muhammad Alif; Borzehandani, Mostafa Yousefzadeh; AbdulRahman, Mohd Basyaruddin; Abdelmalek, Emilia (Nigerian Society of Physical Sciences, 2024)
The ever-increasing consumption of fossil fuels to meet up with the global economic and industrial energy needs has led to climatic change due to uncontrollable emission of a major greenhouse gas (CO2). As a way of mitigating the amount of CO2 in the atmosphere, search for effective and efficient solid adsorbent has been at the front burner of current scientific research. A class of solid adsorbent known as metal organic frameworks (MOFs) have demonstrated immense potentials for CO2 adsorption due to its porous, high thermal and chemical stability, high versatility and ease of production. Upon functionalization, the adsorption efficiency of this class of materials was found to improve tremendously. In this review, the CO2 capture and sequestration potentials of three MOFs (UiO-66, HKUST-1, and MOF-5) and their composites were investigated in the search for economical, stable, and highly selective novel adsorbents for CO2 adsorption. © 2023 The Author(s).